Ayurveda and Modern Perspective on Rajonivritti w.s.r. to Menopause: Review Based on Literary Study - Kumari, Monika; Dixit, Mahesh; Meena, Narendra Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Menopause, a phenomenon unique to women, is the ending of a woman’s monthly menstrual period and ovulation. It, alongside, several other changes in the body and mind, brought in due to a decline in the amount of the hormones estrogen and progesterone being produced by the body. Menopause is, occasionally, viewed as an end to youth and sexuality, making it a socially unacceptable occurrence. Menopause, though, one of the important physical and mental milestones in a woman’s life, many women lack information about what is taking place and what are their options. There comes the role of Ayurveda , in Ayurveda literature there is no detailed description of Rajonivritti or menopause except the age of Rajonivritti is given as 50 years. Ayurveda involves a holistic physiological system based on balance, with its cardinal doctrine of human physiology being constituted by “vata”, “pitta” and “kapha”. In modern medicine the only treatment for these symptoms is Hormone replacement therapy (HRT), which is not a long-term therapy to be given as it has side effects on the overall health of the women. In Ayurveda Dhatu kshaya can be treated with Rasayana therapy and other symptoms of hypo-estrogenic conditions can be treated with Phytoestrogens. So, Ayurveda gives a non-hormonal and cost-effective treatment for Rajonivritti or Menopause.